Insulators recruit histone methyltransferase dMes4 to regulate chromatin of flanking genes. (10th June 2014) - Lhoumaud, Priscillia; Hennion, Magali; Gamot, Adrien; Cuddapah, Suresh; Queille, Sophie; Liang, Jun; Micas, Gael; Morillon, Pauline; Urbach, Serge; Bouchez, Olivier; Severac, Dany; Emberly, Eldon; et al.
Abstract Chromosomal domains in Drosophila are marked by the insulator‐binding proteins (IBPs) dCTCF/Beaf32 and cofactors that participate in regulating long‐range interactions. Chromosomal borders are further enriched in specific histone modifications, yet the role of histone modifiers and nucleosome dynamics in this context remains largely unknown. Here, we show that IBP depletion impairs nucleosome dynamics specifically at the promoters and coding sequence of genes flanked by IBP binding sites. Biochemical purification identifies the H3K36 histone methyltransferase NSD/dMes‐4 as a novel IBP cofactor, which specifically co‐regulates the chromatin accessibility of hundreds of genes flanked by dCTCF/Beaf32. NSD/dMes‐4 presets chromatin before the recruitment of transcriptional activators including DREF that triggers Set2/Hypb‐dependent H3K36 trimethylation, nucleosome positioning, and RNA splicing. Our results unveil a model for how IBPs regulate nucleosome dynamics and gene expression through NSD/dMes‐4, which may regulate H3K27me3 spreading. Our data uncover how IBPs dynamically regulate chromatin organization depending on distinct cofactors.